2015
DOI: 10.1155/2015/520179
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella enterica: Survival, Colonization, and Virulence Differences among Serovars

Abstract: Data indicate that prevalence of specific serovars of Salmonella enterica in human foodborne illness is not correlated with their prevalence in feed. Given that feed is a suboptimal environment for S. enterica, it appears that survival in poultry feed may be an independent factor unrelated to virulence of specific serovars of Salmonella. Additionally, S. enterica serovars appear to have different host specificity and the ability to cause disease in those hosts is also serovar dependent. These differences among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
313
0
12

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 365 publications
(333 citation statements)
references
References 157 publications
8
313
0
12
Order By: Relevance
“…Salmonella species are facultative intracellular bacteria, capable of invading, surviving, and oft en multiplying within diverse eukaryotic cell types, including epithelial and phagocytic cells (21). Adhesion to the intestinal epithelial surface is a key step in pathogenesis and is central to colonisation of the intestine (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…Salmonella species are facultative intracellular bacteria, capable of invading, surviving, and oft en multiplying within diverse eukaryotic cell types, including epithelial and phagocytic cells (21). Adhesion to the intestinal epithelial surface is a key step in pathogenesis and is central to colonisation of the intestine (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that S. Enteritidis has taken the ecologic niche previously occupied by S. Gallinarum in poultry flocks, via the mechanism of competitive exclusion, due to their antigenic similarity (Rabsch et al, 2000). Clearing the commercial flocks from S. Gallinarum enabled S. Enteritidis to colonize chickens without signs of disease (Andino and Hanning, 2015). In addition, serovar Enteritidis has a wider spectrum of natural reservoirs which makes it easier to persist on the farms.…”
Section: The Prevalence Of Salmonella Serovars In Poultry Flocksmentioning
confidence: 99%
“…Salmonella can also leads to severe condition like sepsis and death especially in infants and immunocompromised adults 43 . Other than gastroenteritis, Salmonella may also cause extra intestinal infection like meningitis, osteomyelitis, arthritis, pneumonia, cholecystitis, peritonitis, pyelonephritis, endocarditis, pericarditis, vasculitis and chronic condition like aseptic arthritis and Reiter's syndrome 44 . The predominant serovars of Salmonella, having public health importance are mainly S. Enteritidis and S. Typhimurium 1.…”
Section: Public Health Significance Of Salmonellosismentioning
confidence: 99%